Specyfika wyceny zakładów ubezpieczeń metodą zdyskontowanych przepływów gotówkowych - Jaworski, Witold (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Changes in the insurance market force more focus on shareholder value, and therefore on t standing valuation methods and value drivers of insurance companies. DCF valuation is a key approach, however it requires some adjustments compared to other industries. The article presents major valuation adjustments in the DCF valuation process, specific for valuation of insurance companies: reversed "production process" in insurance business, importance of equity requirements, gearing / leverage levels, adequacy of insurance provisions, incorporation of investment activities as a part of operating cash flows. Taking into account all the specific needs of the insurance valuation, a simplified valuation structure has been presented. Additionally, a summary of key differences between equity valuation (insurance and banking) and entity valuation (non financial institutions) have been presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 210-217